ORGANIZATIONAL RESILIENCE AND CORPORATE PERFORMANCE IN NIGERIAN AIRLINE INDUSTRY (Academicia Globe: Inderscience Research, 2023)
This study examined the effect of organisational resilience on corporate performance in the Nigerian airline industry. The descriptive survey research design adopted the cross-sectional strategy to generate primary data from the respondents. The population consisted of senior staff of domestic airlines in Nigeria.